PERAN DINAS PERHUBUNGAN KOTA SURABAYA DALAM PENERAPAN KEBIJAKAN PARKIR ZONA DI KAWASAN TUNJUNGAN KOTA SURABAYA - Gugun Septian Geopani Silalahi; Oktarizka Reviandani (Halu Oleo University, 2025)
This study aims to analyse the implementation of the zoned parking policy in the Tunjungan area of Surabaya City using the theoretical framework of policy implementation according to George C. Edwards III, which includes four key variables: communication, resource availability, implementer disposition, and bureaucratic structure. A descriptive qualitative research approach was applied through field observations, in-depth interviews with policy implementers, and related document studies. The research findings indicate that the communication and resource provision aspects have been running relatively well. However, there are several obstacles in the implementer disposition aspect, such as weak coordination between officers and attitudes that do not fully support consistent policy implementation. In addition, fragmentation in the bureaucratic structure hinders synergy and clear division of tasks between related agencies, thus affecting the effectiveness of the overall policy implementation.